2014
DOI: 10.1021/ct500838h
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient Calculation of Electronic Absorption Spectra by Means of Intensity-Selected Time-Dependent Density Functional Tight Binding

Abstract: During the last two decades density functional based linear response approaches have become the de facto standard for the calculation of optical properties of small and medium-sized molecules. At the heart of these methods is the solution of an eigenvalue equation in the space of single-orbital transitions, whose quickly increasing number makes such calculations costly if not infeasible for larger molecules. This is especially true for time-dependent density functional tight binding (TD-DFTB), where the evalua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 55 publications
2
62
0
Order By: Relevance
“…However, previous studies have shown that the TD-DFTB method on conjugated systems such as C 60 produces reasonably good agreement with the experimental values. 22,23 …”
Section: Computational Methodologymentioning
confidence: 99%
“…However, previous studies have shown that the TD-DFTB method on conjugated systems such as C 60 produces reasonably good agreement with the experimental values. 22,23 …”
Section: Computational Methodologymentioning
confidence: 99%
“…Calculation of spin-orbit coupling was interfaced by Gao et al [144] for TD-DFT approaches, including TD-DFTB. From a computational efficiency point of view, intensity-selected TD-DFTB has been introduced by Rüger et al [145], delivering similar accuracy as the linear response TD-DFTB, but at a lower computational cost. More details about the TD-DFTB method as well as some other examples of applications can be found in the review paper of T. A. Niehaus [146].…”
Section: Excited States and Time-dependent Dftbmentioning
confidence: 99%
“…Alternatively the excitation space could be truncated by selecting the single-orbital transitions with the highest oscillator strengths down to a certain threshold as proposed in Ref. 42 . If the active space is chosen reasonably, the only side-effect is a small systematic increase in the excitation energies as shown in the appendix A.…”
Section: A Tight-binding Td-dftmentioning
confidence: 99%